2020
DOI: 10.1090/spmj/1594
|View full text |Cite
|
Sign up to set email alerts
|

Note on an eigenvalue problem for an ODE originating from a homogeneous $p$-harmonic function

Abstract: We discuss what is known about homogeneous solutions u to the p− Laplace equation, p fixed, 1 < p < ∞, when (A) u is an entire p− harmonic function on Euclidean n space, R n , or (B) u > 0 is p− harmonic in the cone, K(α) = {x = (x 1 ,. .. , x n) : x 1 > cos α |x|} ⊂ R n , n ≥ 2, with continuous boundary value zero on ∂K(α) \ {0} when α ∈ (0, π]. We also outline a proof of our new result concerning the exact value, λ = 1 − (n − 1)/p, for an eigenvalue problem in an ODE associated with u when u is pharmonic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The literature [2] also improves the PM model by proposing a tensortype diffusion model, who mainly uses the diffusion tensor to replace the diffusion coefficient function in the PM model, although this improved model mainly addresses images with flow-like structures like fingerprints, which can be well enhanced for this class of images. In the literature [3,4], it was found that the edge and slope regions of an image can be identified by differential curvature, and both constructed two adaptive diffusion coefficients to discriminate the whole image. In the literature [5], a nonlinear anisotropic combined diffusion model was designed; this model is mainly by choosing different diffusion methods when facing different regions of the image, homogeneous diffusion for smooth regions, and mean curvature diffusion for edge regions, and the effectiveness of this model was experimentally demonstrated.…”
Section: Related Studiesmentioning
confidence: 99%
“…The literature [2] also improves the PM model by proposing a tensortype diffusion model, who mainly uses the diffusion tensor to replace the diffusion coefficient function in the PM model, although this improved model mainly addresses images with flow-like structures like fingerprints, which can be well enhanced for this class of images. In the literature [3,4], it was found that the edge and slope regions of an image can be identified by differential curvature, and both constructed two adaptive diffusion coefficients to discriminate the whole image. In the literature [5], a nonlinear anisotropic combined diffusion model was designed; this model is mainly by choosing different diffusion methods when facing different regions of the image, homogeneous diffusion for smooth regions, and mean curvature diffusion for edge regions, and the effectiveness of this model was experimentally demonstrated.…”
Section: Related Studiesmentioning
confidence: 99%
“…An important structure property of any Jordan algebra V is that the spectrum of any idempotent is a subset of {0, 1 2 , 1}. In particular, V admits the so-called Peirce decomposition:…”
Section: Jordan Algebras Jordan Algebras Is An Important Class In The...mentioning
confidence: 99%
“…The eigenvalue 1 2 and the corresponding subspace is distinguished in many ways. For example, a Jordan algebra is simple if and only its 1 2 -eigenspace is nontrivial for any idempotent. Moreover, V 1 2 satisfies the Jordan fusion laws…”
Section: Jordan Algebras Jordan Algebras Is An Important Class In The...mentioning
confidence: 99%
See 2 more Smart Citations